Improving Productivity in the Warehouse Area through Inventory Management in an Agroindustrial Company in Motupe, Peru - Becerra Carrillo, Nayeli Y. (2025)
The objective of this research was to implement inventory management to improve productivity in the warehouse area of an agro-industrial company Motupe. The research is of an applied type with a descriptive scope of quasi-experimental design, using instruments for data collection such as interviews with the warehouse manager and collaborators, as well as documentary analysis for the collection of both variables. Diagnostic tools such as Ishikawa and Pareto diagrams were applied to identify problems such as disorder and lack of cleanliness, absence of signage, absence of productivity indicators, poor material control, lack of training, and non-standardized processes. It was proposed to implement the 5S technique, ABC classification, determine productivity indicators, create material output control forms, create a training plan, and design a dispatch process. In the last three months, efficiency was 94%, effectiveness was 91%, resulting in 85% productivity in the warehouse area. It is concluded that, with the implementation of inventory management, efficiency improved by 17%, effectiveness by 20%, and productivity by 31%.